Makna Teologi Buddha Djawi Wisnu Dalam Kitab Weddo Djojo Sampurno - I Made Sukma Manggala; I Nyoman Suarka; Ida Bagus Rai Putra (Jayapangus Press, 2022)
Djawi Vishnu Buddhists’ belief teaches its followers to respect and love those who intercede for God's will as a result the individual self exists in this world. If there is an imbalance between the Bhuwana Agung (the universe) and Bhuwana Alit (the human self) a catastrophe can occur in the lives of Djawi Vishnu Buddhists. The text of the Weddo Djojo Sampurno book contains several quotes that emphasize the beauty of nature as a reflection of the Bhuwana Agung and the sincerity of meditation as a reflection of Bhuwana Alit. This aims of this study is to figure out the Buddhist theology of Djawi Vishnu as a discourse of worship presented to Gusti Hulun Hyang Bhatara Wisnu in his manifestation as the ruler of the universe based on love and compassion. The love and affection intended are capable of loving oneself or Ingsun who is aware of the existence of the universe as a place to interact with other living things. The theory applied in this study is the semiotic theory proposed by Roland Barthes in terms of the meaning of the second level. The data being applied was qualitative data. Further, primary data sources are manuscripts, Weddo Djojo Sampurno books and secondary data sources include research results, books, internet sources. The research instruments were a dictionary as a medium for translating Javanese text into the target language translation. At the stage of presenting the results of this research data analysis were analyzed using formal methods and informal methods. As a result, it was found that the sincerity of meditation based on compassion as a form of controlling the concentration of the mind towards Gusti was aimed at the highest awareness. It is when humans are able to realize who they are and focus their minds on one single goal (moksa) to unite with Hyang Gusti.